Unraveling the impact of nonmagnetic Sc substitution on the magnetic properties of La2NiMnO6 double perovskite. (4th February 2021) - Nasir, Mohammad; Khan, Mahmud; Bhatt, Subhash; Patra, Nirmalendu; Bhattacharyya, Dibyendu; Sen, Somaditya
Abstract: The structural, electronic, and magnetic properties of a sol-gel prepared series of La2 Ni1− x Sc x MnO6 compounds have been extensively studied using x-ray diffraction, x-ray absorption near edge structure, and dc magnetization techniques, respectively. The entire series was isostructural and exhibited the La2 NiMnO6 double perovskite P21 /n monoclinic structure. The nonmagnetic Sc 3+ substitution led to the evolution of competing magnetic phases in La2 Ni1− x Sc x MnO6 . The substitution also caused an increase in lattice parameters, cell volume, and bond lengths. Consequently, Sc 3+ dilution resulted in a dramatic decrease in Curie temperature, suggesting a reduction in the strength of the Ni 2+ –O 2− –Mn 4+ superexchange ferromagnetic interaction. The Sc 3+ substitution generated antisite defects, which significantly suppressed the saturation magnetization of the system. The competing magnetic interactions observed in the La2 Ni1− x Sc x MnO6 system are discussed in terms of cation disorder, cation valances, and changes in the bond lengths/angles, caused by the Sc 3+ substitution.